Let the love begin (GMA Films, 2005)
It all begins in high school. Pia is beautiful and wealthy. Shes the campus sweetheart and the girl of every guys dreams. Eric is handsome and intelligent, but poor. He is forced to work as a janitor in Pia's high school where he admires her from afar. Although belonging to the extemes of the social strata, their worlds cross when they share the same seat in class Pia during the day and Eric at night as part of a scholarship program.Is this a sign that they are destined for each other? Can a humble janitor even dream of being loved by a wealthy, lovely lady?